THE IMPACT OF BANKING ACTIVITY INDICATORS ON THE RETURN ON DEPOSITS, APPLIED RESEARCH A SAMPLE OF IRAQI COMMERCIAL BANKS - Dr . Lecturer Rebin Tayeb Rashid; Raid Hassan Ali; Assist. Prof .Dr. Waad Hadi Abd (American Journals, 2023)
The study aims to demonstrate the effect of theoretical relationships between the variables of banking activity indicators, the investment indicator on deposits and the resource employment indicator, as independent variables with the return on deposits indicator as a dependent variable. Financial analysis on the study sample (the National Bank of Iraq, the Iraqi Middle East Investment Bank, and the Gulf Commercial Bank). And then find the statistical correlation and effect of the high rates of bank deposits and bank loans on bank liquidity by using the statistical analysis program (SPSS.26) to reach the most important results that proved the existence of a relationship of effects that occur in the dependent variable the rate of return on deposits as a result of the influence of the independent sub-variables , as there is a positive relationship between the deposit investment index and the return on deposits for the correlation value (0.906**) at a significant level (0.01), while there is an inverse relationship between the resource employment index and the return on deposits for a correlation value (-0.033) at a significant level (0.01), In addition to the presence of a significant direct effect on the return on deposits of commercial banks, the study sample, as a result of increasing the percentage of deposit investment index by one unit, which is a significant effect of (0.000) at a significant level of less than (5%) While there is an insignificant direct effect on the return on deposits as a result of increasing the resource employment index by one unit and by (12%), which is more than (5%).
Keywords: deposit investment index, resource employment index, rate of return on deposits.